Eurorégió-vázlatok a magyar–osztrák–szlovák határmenti térségben - Rechnitzer, János (Tér és Társadalom, 1997)
The purpose of this study is to analyse the cross-boundary relationships in the Hungarian-Austrian-Slovakian border region and outline the new types of the collaboration. Austrian investors represented mainly by small and medium scale companies stimulate the economic links. Their activity involves considerable trading between the countries: about one-fourth of the export and import activity of the analysed Hungarian counties is related to Austrian partners. This proportion seems to be stable now. The relations to the Slovakian economy have just restored and they have a scarce effect on the Hungarian counties. The institutions of the cross-border collaboration are established at national and regional level. Their operation is supported by the financial resources of the Phare CBC program between 1995 and 1999. Organisations of the Slovakian-Hungarian co-operation have not been set up yet. Cross-border relations are random, they exist at the level of particular institutions. The author summarised the conditions of the future co-operation. He emphasised the significant differences of the spatial structure of the involved regional economies (particularly, the dominant role of Vienna). The incompatibility of the units of regional decision-making (counties, provinces) and different perspectives of regional development in the three regions may render the progress more difficult. Despite the conflicts, people living nearby the borders and the actors of regional development are in day-by-day contact. The net of these relations may be the hasis of an Euroregion. The author distincts two possible versions of a potential Hungarian-Austrian-Slovakian Euroregion. The first model is based on the medium levei of the spatial administration. The second one consists of the attraction zones of Vienna (Austria), Bratislava (Slovakia), Győr and Sopron (Hungary). The cities would share the central functions of the Euroregion. To stimulate the cross-border relations, it would be necessary to improve the transportation links, support the economic co-operation and make the actors of the regional development aware of the advantages of the collaboration.